2013
DOI: 10.1007/s12070-013-0646-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Outcome of the Orbital Complications Due to Acute Infective Rhino Sinusitis

Abstract: To describe the clinical presentation and visual outcome of patients with orbital complications of acute infective rhino sinusitis. This is a retrospective case series of patients diagnosed with of orbital involvement due to acute infective rhino sinusitis, who presented to eye OPD between July 2007 and July 2009. The medical records were reviewed with particular emphasis on clinical presentation and management. Twelve patients with an average age of 40.3 years (range, 14-65 years) were studied. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 4 publications
3
14
1
Order By: Relevance
“…Reported rates of an associated sinusitis with orbital cellulitis varied from 15 to 100% [913]. In the current study, orbital trauma was present in 13.7% of patients.…”
Section: Discussionmentioning
confidence: 46%
“…Reported rates of an associated sinusitis with orbital cellulitis varied from 15 to 100% [913]. In the current study, orbital trauma was present in 13.7% of patients.…”
Section: Discussionmentioning
confidence: 46%
“…Orbital cellulitis, frequently presenting secondary to paranasal sinusitis, is seen in both the pediatric and adult populations. [1][2][3] Due to the close relationship of the orbit to the paranasal sinuses, appropriate management and early diagnosis are critical to avoid serious complications that may jeopardize the integrity of the orbit and intracranial structures, resulting in permanent vision loss, optic neuropathy, cavernous sinus thrombosis, brain abscess, meningitis, and possibly death. 1,4,5 Chandler et al 4 first described the classification of orbital infections in 1970 that is still referenced today.…”
Section: Introductionmentioning
confidence: 99%
“…8 In another retrospective study by Saroj Gupta 83.3 % patients presented with orbital cellulites as a complication of acute infective rhino sinusitis. 9 Age group in our study varied from 19 to 70 years with a mean of 54.85. Majority of the patients had fungal sinusitis which is common in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 98%
“…In a two year retrospective study of 12 patients Gupta reported that the most common presenting symptom was diminution of vision (66.6%) followed by proptosis, ptosis (33.3%) and globe displacement (16.6%). 9 The most common orbital complication noted was orbital cellulitis (83.3%). Majority of the patients had multiple sinus involvement.…”
Section: Discussionmentioning
confidence: 99%